THE ROLE OF MATHEMATICAL PROBLEMS IN FORMING STUDENTS’ INDEPENDENT THINKING SKILLS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the role and significance of mathematics, in particular, mathematical problems, in the formation of students ' independent thinking skills. Independent thinking is considered as one of the main goals of modern education, and the role of mathematical issues in the development of analytical andlogical thinking is highlighted in the formation of this skill. The article is based on the fact that different types of issues (arithmetic, logical, vital, open type) have different effects on the thinking of readers. Also covered are methodological approaches that serve to stimulate the creative and critical thinking of students — such forms of active education as creating problem situations, creating issues, working in a group, exchanging ideas, drawing logical conclusions. Through the practical examples presented in the article, the role of mathematical problems in the formation of not only theoretical knowledge, but also vital skills is shown. Results of this study mathematics textbook